2021
DOI: 10.1021/acsestwater.1c00173
|View full text |Cite
|
Sign up to set email alerts
|

Can Smart Stormwater Systems Outsmart the Weather? Stormwater Capture with Real-Time Control in Southern California

Abstract: Stormwater capture systems have the potential to address many urban stormwater management challenges, particularly in water-scarce regions like Southern California. Here, we investigate the potential best-case limits of water supply and stormwater retention benefits delivered by a 10,000 m 3 stormwater capture system equipped with real-time control (RTC) on a university campus in Southern California. Using a copula-based conditional probability analysis, two performance metrics (percent of water demand satisfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…We then found the probability density function (PDF) of temperature conditioned on a specified high precipitation value: fX|Y(x|y)=c[]FX(x),FY(y)·fX(x) ${f}_{X\vert Y}(x\vert y)=c\left[{F}_{X}(x),{F}_{Y}(y)\right]\cdot {f}_{X}(x)$ where c represents the copula PDF and f X (x) is the marginal temperature PDF (Madadgar et al., 2017; Parker et al., 2022). The resulting PDF represents the conditional distribution of temperature at the high precipitation value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then found the probability density function (PDF) of temperature conditioned on a specified high precipitation value: fX|Y(x|y)=c[]FX(x),FY(y)·fX(x) ${f}_{X\vert Y}(x\vert y)=c\left[{F}_{X}(x),{F}_{Y}(y)\right]\cdot {f}_{X}(x)$ where c represents the copula PDF and f X (x) is the marginal temperature PDF (Madadgar et al., 2017; Parker et al., 2022). The resulting PDF represents the conditional distribution of temperature at the high precipitation value.…”
Section: Methodsmentioning
confidence: 99%
“…where c represents the copula PDF and f X (x) is the marginal temperature PDF (Madadgar et al, 2017;Parker et al, 2022). The resulting PDF represents the conditional distribution of temperature at the high precipitation value.…”
Section: Maximum Temperature or Vpd Probability Distributions Given H...mentioning
confidence: 99%
“…Results showed clear benefits in pollution reduction. A simulated runoff model using a stormwater tank with real-time control for capture and storage on a college campus 64 highlighted the benefits of SWH for water supply and flood risk reduction based on rainfall event prediction, precipitation, and tank size simulation.…”
Section: Harvested Stormwatermentioning
confidence: 99%
“…One important driver of implementation relates to the costs and benefits of RTC RWH systems. While the cost of such system is context specific, several studies have concluded that rainwater storages retrofitted by RTC technology is a more cost-effective solution when broader criteria, such as flood control and environmental benefits, are considered (Melville-Shreeve et al, 2016;Parker et al, 2022). Additional benefits could also be obtained from the coordinated control of multiple rainwater storages at network scale given the synergies it can provide.…”
Section: Implementation At Catchment-scalementioning
confidence: 99%